A Pretreatment CT Model Predicts Survival Following Chemolipiodolization in Patients With Hepatocellular Carcinoma. (19th July 2019) - Zhang, Yijun; Qu, Shuping; Yi, Wanwan; Zhai, Jian; Zhang, Xiaobing; Wei, Lixin; Lau, Wan Yee; Wu, Mengchao; Shen, Feng; Fan, Hengwei; Wu, Dong
Purpose: To establish a computed tomography–based prognostic model for patients with hepatocellular carcinoma treated with transarterial chemoembolization. Materials and Methods: Using prospectively collected data from 195 consecutive patients with hepatocellular carcinoma who underwent chemolipiodolization at the Eastern Hepatobiliary Surgery Hospital between 2013 and 2016, we established a prognostic model based on hepatocellular carcinoma enhancement patterns on computed tomography scans to predict the outcome of transarterial chemoembolization. Furthermore, a histopathology analysis was performed on 108 different patients undergoing resection between 2014 and 2016 to identify whether there was a correlation between enhancement pattern and microvessel density. Results: The prognostic model classified hepatocellular carcinoma into 3 types: type I, which reached peak enhancement during the arterial phase and had a high mean microvessel density (101.5 vessels/0.74 mm 2 ); type II, which reached peak enhancement during the portal venous or delayed phase and had an intermediate microvessel density (53.6 vessels/0.74 mm 2 ); and type III, in which the tumor was insignificantly enhanced and had a low microvessel density (21.1 vessels/0.74 mm 2 ). For type I, II, and III hepatocellular carcinoma, the post-transarterial chemoembolization 1-year tumor complete necrosis rates were 13.7%, 36.5%, and 0%, respectively ( P < .001), and the 3-year overall survival rates were 14.1%, 38.6%, and 0%, respectively ( P < .001). Conclusion: Our results indicate that hepatocellular carcinoma type is an independent predictor of complete necrosis and overall survival